A competency~based approach to communication management as applied to the South African business environment - Theresa Claassen; Sonja Verwey (Communicare)
Change in the external environment, without exception, impacts upon the organisation and in particular the practising of public relations. Since the beginning of the nineties, the South African business environment Is characterised by the redefinement of business practices and partners and the shifting of boundaries as an expression of the globalization of the world economy. The lifting of sanctions, together with the events that took place in the political arena, introduced unprecedented changes in the legal-political, economic and social environments. Against this background, an urgent need for the development of a context sensitive generic framework of required outputs for communication managers in a changing business envlronment, based on an integrated approach, was identified. This article provides an overview of the dynamics of change in the external environment and the impact it has on the public relations function. A brief discussion regarding standard setting as envisaged by the National Qualifications Framework (NQF) and the professionalisation of public relations, with specific reference to training needs and accreditation, is included. The article also attempts to provide Insight into the empirical process that led to the development of a generic framework and the hierarchial classification of outputs according to levels of work.